The Cambridge Companion To International Law - Siswandi, Achmad Gusman (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2014)
This book provides a thorough introduction to international law in a way that is rather unique compared to similar references. The subject matteris divided in a more concise way, while still giving rich perspective as it covers not only theories but also case studies and practices. This book consists of four parts, namely: the contexts of international law; international law and the state; techniques and arenas; and projects of international law.Â DOI: https://doi.org/10.22304/pjih.v1n2.a11